Why men are the minority: The perceptions of young men in UK post-primary education about studying psychology at university - Elida Cena; Stephanie Burns; Ruth Lee; Kathryn Gillespie; Patrick A. O’Connor; Tara Anderson; Grace Duffy; Lisa Graham-Wisener (PLoS ONE, 2025)
Psychology is categorised as a science by most higher education authorities internationally. As with many science, mathematics and engineering fields, women are underrepresented in psychology at senior levels (the ‘leaky pipeline’). However, it is men who are underrepresented within the discipline overall, meaning that the psychology workforce does not reflect the population it aims to serve. It is important to understand why fewer men are opting to enter the profession, beginning with their choices regarding higher education. The current study is one of the first to qualitatively examine the perceptions and motivations of adolescent and young adult men in post-primary education of the study of psychology at university undergraduate level. Twelve focus groups were conducted with young men (n = 64) studying AS or A2-Levels, between 16 and 18 years of age, in post-primary schools in a UK region, Northern Ireland (NI). Thematic analysis demonstrated that psychology was viewed in a gendered way as a ‘feminine’, ‘soft’ subject dealing with emotions, and was not perceived as an ‘objective’, ‘fact-based’ science. The lack of male role models in psychology was a barrier to young men pursuing psychology at university level. Young men, whether currently studying psychology at school or not, expressed gendered career expectations and motivations. There are opportunities for targeted efforts with young men to promote psychology as a science and a multi-faceted discipline. Findings will inform the efforts of those in post-primary and higher education level in making psychology inclusive in terms of gender and improving the diversity of psychology as a field.